1999
DOI: 10.1029/1999gl008348
|View full text |Cite
|
Sign up to set email alerts
|

Lunar orbital evolution: A synthesis of recent results

Abstract: Abstract. The present rate of tidal dissipation in the EarthMoon system is known to be anomalously high, in the sense that the implied age of the lunar orbit is only 1.5 x 109 years, though other evidence suggests an age closer to 4x 109 years. To assess how long the anomalous dissipation has persisted, we use published estimates of lunar orbital configurations derived from (a) fine grained sediments containing tidal laminations and (b) numerical ocean models averaged over varying ocean geometries. The implied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
82
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 36 publications
5
82
0
1
Order By: Relevance
“…Third, we assumed constant tidal properties for Earth throughout the calculation, which is in conflict with the fact that the current rate of the Moon's tidal recession is about three times higher than the long-term average 35 . An increase in the tidal dissipation within Earth's oceans over time as suggested by modeling 36,37 would mean that the Moon spent more time at the Cassini state transition than we calculated, allowing more damping of inclination. These factors are all independent of the fact that the Moon may not have been in synchronous rotation during the Cassini state transition, as discussed in this work.…”
mentioning
confidence: 84%
“…Third, we assumed constant tidal properties for Earth throughout the calculation, which is in conflict with the fact that the current rate of the Moon's tidal recession is about three times higher than the long-term average 35 . An increase in the tidal dissipation within Earth's oceans over time as suggested by modeling 36,37 would mean that the Moon spent more time at the Cassini state transition than we calculated, allowing more damping of inclination. These factors are all independent of the fact that the Moon may not have been in synchronous rotation during the Cassini state transition, as discussed in this work.…”
mentioning
confidence: 84%
“…Of course, the tidal interactions in the Earth−Moon system have caused a gradual expansion of this orbit, but there is a large uncertainty over the integrated amount of this acceleration over the previous 4 Gyr. We base our estimate on results by Bills & Ray (1999) and use a semi-major axis for the Moon that is one half of the present value, that is, about 182 000 km. For simplicity, we take this orbit to be circular and situated in the ecliptic plane.…”
Section: Lunar and Planetary Orbitsmentioning
confidence: 99%
“…Also, theories have suggested that because of tidal energy dissipation, the Moon has been receding from the Earth. Recent theoretical studies concluded that the distance between the Earth and the Moon was about half of the present distance circa 4 Ga ago (2,3). These theoretical conclusions suggest the possibility that there has been interaction between the Earth's atmosphere and the near-side lunar surface in ancient time.…”
mentioning
confidence: 85%
“…For example, in the case of the EW, about 10 3 O ϩ ions per cm 2 are estimated to hit the lunar surface according to the Geotail observation (6). Assuming that this flux was implanted into an ilmenite grain for 1.5 ϫ 10 5 years of a mean surface exposure time (34) 3 . Considering large uncertainties in observed values used in the above estimation such as the escaping O ϩ flux and the interacting SW intensity, a factor of 10 difference between the 2 estimates in the oxygen concentration can reasonably be tolerated.…”
Section: Prescription For Experimental Proceduresmentioning
confidence: 99%